Intravenous nicardipine and labetalol use in hypertensive patients with signs or symptoms suggestive of end-organ damage in the emergency department: a subgroup analysis of the CLUE trial - Brian Hiestand; Phillip Levy; W Frank Peacock; Brigitte M Baumann; Richard M Nowak; Amy Hsu; Joseph Varon; Chad M Cannon; David M Cline; Pierre Borczuk; Abhinav Chandra; Deborah B Diercks; et al. (BMJ Open)
Objective To compare the efficacy of Food and Drug Administration recommended dosing of nicardipine versus labetalol for the management of hypertensive patients with signs and/or symptoms (S/S) suggestive of end-organ damage (EOD).Design Secondary analysis of the multicentre prospective, randomised CLUE trial.Setting 13 academic emergency departments in the USA.Participants Eligible patients had two systolic blood pressure (SBP) measures ≥180 mm Hg at least 10 min apart, no contraindications to nicardipine or labetalol and predefined S/S suggestive of EOD on arrival.Interventions Medications were administered by continuous infusion (nicardipine) or repeat intravenous bolus (labetalol) for a study period of 30 min or until a specified target SBP ±20 mm Hg was achieved.Primary outcome measure Percentage of participants achieving a predefined target SBP range (TR) defined as an SBP within ±20 mm Hg as established by the treating physician.Results Of the 141 eligible patients, 49.6% received nicardipine, 51.7% were women and 81.6% were black. Mean age was 52.2±13.9 years. Median initial SBP did not differ in the nicardipine (210.5 (IQR 197–226) mm Hg) and labetalol (210 (200–226) mm Hg) groups (p=0.862). Nicardipine patients were more likely to have a history of diabetes (41.4% vs 25.7%, p=0.05) but there were no other historical, demographic or laboratory differences between groups. Within 30 min, nicardipine patients more often reached the target SBP range than those receiving labetalol (91.4% vs 76.1%, difference=15.3% (95% CI 3.5% to 27.3%); p=0.01). On multivariable modelling with adjustment for gender and clinical site, nicardipine patients were more likely to be in TR by 30 min than patients receiving labetalol (OR 3.65, 95% CI 1.31 to 10.18, C statistic=0.72).Conclusions In the setting of hypertension with suspected EOD, patients treated with nicardipine are more likely to reach prespecified SBP targets within 30 min than patients receiving labetalol.Clinical Trial Registration NCT00765648, clinicaltrials.gov